Cutaneous Leishmaniasis: epidemiological overview in the Brazilian Northeast region, Greater São Luís Metropolitan Region (2010-2020) (Research, Society and Development, 2022)
Introduction: Cutaneous Leishmaniasis is a parasitic disease that has a high incidence in tropical and subtropical regions. Over the years it presents high expansion in all Brazilian regions, with emphasis on the North and Northeast, which shows vulnerable populations as the most affected. Investigating the epidemiology of these diseases is essential for the formulation and implementation of public health policies with the objective of preventing and combating the insect vector. Objective: To describe epidemiological data and their relationship with sociodemographic variables in relation to the incidence of Cutaneous Leishmaniasis in the Greater São Luís Metropolitan Region between the years 2010 to 2020. Methodology: Epidemiological study with a quantitative and retrospective approach which used secondary data in relation to confirmed cases of the disease between the years 2010 to 2020 for the study region and qualitative variables. Results: The data showed a higher incidence of the disease in male individuals, of mixed race and with incomplete primary education. Conclusion: Actions developed by the public spheres with the objective of disseminating preventive campaigns associated with financial and technical investment to universities and research centers contribute to the development of researches and the elaboration of measures that act in the interfaces of prevention, treatment, control and eradication of major neglected tropical diseases.